Dual topology for partitioning of water distribution networks considering actual valve locations. Issue 7 (9th August 2019) - Santonastaso, G. F.; Di Nardo, A.; Creaco, E.
ABSTRACT: This paper proposes a general framework to adjust water distribution network (WDN) partitioning algorithms to account for the real positions of isolation valves. It is based on changing the reference WDN topology, on which partitioning algorithms typically operate. Specifically, the WDN topological description based on nodes and pipes must be replaced with a dual topology based on WDN segments and isolation valves. A generic partitioning algorithm can then be applied to the dual topology. As a result, DMAs are obtained by merging adjacent segments while inter-DMA boundary pipes are forced to be selected among the valve-fitted pipes that separate segments. This framework enables obtaining feasible WDN partitioning solutions, which do not need additional isolation valves to be installed. The applications of the novel framework to three WDN partitioning algorithms prove its effective applicability in one explicatory WDN and two WDNs of the real world.